1984
DOI: 10.1097/00004032-198406000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 240Pu/239Pu Ratio in Environmental Samples Based on the Measurement of Lx/alpha-ray Activity Ratio

Abstract: The determination of the 240Pu /239Pu isotopic ratio in environmental samples has been attempted by the measurement of the Lx/alpha-ray activity ratio using a Ge- LEPS (low-energy photon spectrometer) and a surface-barrier Si detector. By this method, interesting data were obtained for various samples collected from Thule , Greenland, Bikini Atoll and Nagasaki, as well as for some soils collected from near and off-site locations of atomic power stations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 3 publications
3
25
0
Order By: Relevance
“…Muramatsu et al (2001) and Yamada et al (2007) reported that this higher atom ratio was likely due to close-in fallout Pu originating from the Pacific Proving Grounds (PPGs). For example, the 240 Pu/ 239 Pu atom ratio in soil from Bikini Island was reported to be 0.338 AE 0.0051 (Komura et al, 1984). The 240 Pu/ 239 Pu atom ratio could be lowered by mixing in the sea with Pu isotopes which were deposited directly from the atmospheric environment and transported by rivers and winds through weathering processes from the land (Kim et al, 2003(Kim et al, , 2004Okubo et al, 2008;Yamada and Nagaya, 2000;Yamada et al, 2007;Zheng and Yamada, 2004, 2005a.…”
Section: The Concentration Of 239þ240 Pu In Bottom Sediment Samplesmentioning
confidence: 99%
“…Muramatsu et al (2001) and Yamada et al (2007) reported that this higher atom ratio was likely due to close-in fallout Pu originating from the Pacific Proving Grounds (PPGs). For example, the 240 Pu/ 239 Pu atom ratio in soil from Bikini Island was reported to be 0.338 AE 0.0051 (Komura et al, 1984). The 240 Pu/ 239 Pu atom ratio could be lowered by mixing in the sea with Pu isotopes which were deposited directly from the atmospheric environment and transported by rivers and winds through weathering processes from the land (Kim et al, 2003(Kim et al, , 2004Okubo et al, 2008;Yamada and Nagaya, 2000;Yamada et al, 2007;Zheng and Yamada, 2004, 2005a.…”
Section: The Concentration Of 239þ240 Pu In Bottom Sediment Samplesmentioning
confidence: 99%
“…The nuclear emulsion technique (Sloth and Studier, 1958), internal conversion electron spectroscopy (Shiokawa et al, 1989), and simultaneous counting of alpha particles and U L-shell X-rays (Hisamatsu and Sakanoue, 1984;Komura et al, 1984) have been utilized in measuring the separate activities of 239 Pu and 240 Pu in environmental samples. In addition, thermal neutron activation analysis together with alpha spectrometry has been used for determining the 238 Pu/ 239þ240 Pu activity ratio (Matsunami et al, 1983), as well as high-resolution alpha spectrometry with spectral deconvolution methods (Amoudry and Burger, 1984;Mitchell et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The inventory of anthropogenic long-lived radionuclides in the water column is one of the useful parameters for delineating accumulation and transport processes in the environment (Krey et al, 1976;Koide et al, 1985;Kelley et al, 1999) and that of w0.33 from the Bravo shot fallout (Komura et al, 1984). The horizontal tick marks plotted below the vertical distributions indicate the depth of the bottom.…”
Section: þ240 Pu Activitiesmentioning
confidence: 99%
“…The atom ratio of 240 Pu/ 239 Pu depends upon the specific weapons design and test yield (Warneke et al, 2002). Komura et al (1984) reported the 240 Pu/ 239 Pu atom ratio of 0.338 AE 0.051 in Bikini Island soil, and that of 0.318 AE 0.033 in hemp-palm leaves of fishing floats which were used by the No. 5 Fukuryu-Maru (Lucky Dragon) and exposed to fallout from the ''CASTLE-Bravo'' shot.…”
Section: Contribution Of the Ppg Close-in Falloutmentioning
confidence: 99%
See 1 more Smart Citation